Le tre Europe di Ralf Dahrendorf - Poggiolini, Ilaria (SocietàMutamentoPolitica, 2019)
Reflecting on Dahrendorf’s visions and observations on first, second and third Europe opens new fascinating avenues for the understanding of the present state of the Union and the future of liberalism. His political involvement in Germany and Bruxelles since the late 1960s, and his role as public intellectual and leader of prominent academic institutions, were experienced by Dahrendorf as opportunities to test his ideas of liberal societies, of European cooperation (and democratic deficit) and of the return to democracy of Eastern Central Europe. This essay recontructs and comments on two major historical processes that Dahrendorf witnessed and became involved with: 1) the transformation of first Europe in a much broader project, geographically and politically (la seconda Europa) and the connected process pursuing both widening and deepening on the road of third Europe. 2) the return to West of Communist Eastern Europe leading to 1989: a triumph of the liberal order for Dahrendorf but also a process leading into a deep valley of tears and eventually, in the end, to a democratic post-communist reality. This essay is both a reassessment of Dahrendorf initiatives and ideas in these areas and an attempt at reading present developments on the basis of his thinking.